Climate services user needs assessment: lower Mekong Basin, Cambodia - Phanith, Chou; Bora, Chan Borey; Soksophors, Yim; Khieng, Phanna; Giles, James; Swaans, Kees (2024)
This study explores farmers’ current access to and desired use of climate information and complementary services to support farming decisions throughout the season. This is done by analyzing priority farming systems, key agricultural decisions, current/desired use of (D)CAS+, and digital readiness. Findings from the study may help assess potential challenges and opportunities for the development and scaling of DCAS+ and inform policy and practices around the design, development, adoption, and scaling of these services to cater to farmers' needs.